Pramipexole Increases Go Timeouts but Not No-go Errors in Healthy Volunteers - Yang, Xue Qing; Glizer, Daniel; Vo, Andrew; Seergobin, Ken; MacDonald, Penny A. (Frontiers in Human Neuroscience, 2016)
Parkinson’s disease (PD) is characterized by motor symptoms, such as resting tremor, bradykinesia, and rigidity, but also features non-motor complications. PD patients taking dopaminergic therapy, such as levodopa but especially dopamine agonists (DAs), evidence an increase in impulse control disorders, suggesting a link between dopaminergic therapy and impulsive pursuit of pleasurable activities. However, impulsivity is a multifaceted construct. Motor impulsivity refers to the inability to overcome automatic responses or cancel pre-potent responses. Previous research has suggested that PD patients, on dopaminergic medications, have decreased motor impulsivity. Whether effects on impulsivity are main effects of dopaminergic therapies or are specific to PD is unclear. Using a Go No-go task, we investigated the effect of a single dose of the DA pramipexole on motor impulsivity in healthy participants. The Go No-go task consisted of Go trials, for which keystroke responses were made as quickly as possible, and lesser frequency No-go trials, on which motor responses were to be inhibited. We hypothesized that pramipexole would decrease motor impulsivity. This would manifest as a) fewer No-go errors (i.e., fewer responses on trials in which a response ought to have been inhibited) and b) more timed-out Go trials (i.e., more trials on which the deadline elapsed before a decision to make a keystroke occurred). Healthy volunteers were treated with either 0.5 mg of pramipexole or a standard placebo (randomly determined). During the two-hour wait period, they completed demographic, cognitive, physiological, and affective measures. The pramipexole group had significantly more Go timeouts (p<0.05) compared to the placebo group though they did not differ in percent of No-go errors. In contrast to its effect on pursuit of pleasurable activities, pramipexole did not increase motor impulsivity. In fact, in line with findings in PD and addiction, dopaminergic therapy might increase motor impulse control. In these patient groups, by enhancing function of the dorsal striatum of the basal ganglia in contrast to its effect on impulsive pursuit of pleasurable activities. These findings have implications for use and effects of pramipexole in PD as well as in other conditions (e.g., restless leg, dystonia, depression, addiction-related problems).